INFLUENCE OF WEIGHT FITNESS ON PHYSICAL DEVELOPMENT OF DIFFERENT POPULATION GROUPS: CHARACTERISTICS AND NEEDS - Молотильнікова, В.; Войчун, О. (SWorldJournal, 2023)
The work is devoted to the problem of studying the characteristics of adaptive changes in the human body during weight fitness classes. The relevance of weight fitness for the population is due to the unsatisfactory state of health of the population of Uk